2004
DOI: 10.1080/11250000409356574
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive plasticity of blue tits(Parus caeruleus)and great tits(Parus major)breeding in natural and semi‐natural insular habitats

Abstract: The breeding performance and foraging of blue and great tits, and the abundance of arthropods living on the trees of an oakwood and of a coniferous reafforestation were studied in Sicily, in order to: 1) compare breeding parameters in natural and seminatural habitats within the same area; 2) estimate the degree of overlap in peak resource and peak demand of young tits, and the overlap of nestling diet of the two species in the two habitats. Both species had earlier laying dates, laid more eggs and raised more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Fargallo & Johnstone 1997, Massa et al 2004, Arriero et al 2006, Blondel et al 2006. This suggests that factors other than food or nest parasites cause the low breeding success in the rich, ectoparasite-free, nest environment in the Algerian semi-evergreen oak habitat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fargallo & Johnstone 1997, Massa et al 2004, Arriero et al 2006, Blondel et al 2006. This suggests that factors other than food or nest parasites cause the low breeding success in the rich, ectoparasite-free, nest environment in the Algerian semi-evergreen oak habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Blondel 1985, Clamens et al 1986, Blondel et al 1987, Fargallo & Johnston 1997, Massa et al 2004, Arriero et al 2006, Garcia-Del-Rey et al 2006. Comparative analyses of breeding biology in distinct habitat types at the southern edge of the distribution range reported lower breeding success in European Mediterranean evergreen habitat, often attributed to a significant reduction in caterpillar availability and/or higher loads of nest ectoparasites attacking chicks in these populations (Blondel et al 1991, Chabi et al 1995, Hurtrez-BoussPs et al 1997, Tremblay et al 2003, 2005, Bańbura et al 2004, Massa et al 2004, Arriero et al 2006, Garcia-Del-Rey et al 2006. Studies that controlled for altitude and latitude also reported significantly later adaptive breeding dates in evergreen than in summergreen oak patches (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly, we can divide the work done to date into 1) early descriptive studies (e.g., Gibb & Betts, 1963;Eguchi, 1980) in which very detailed information on feeding habits during the breeding season is given, but in most cases with relatively small sample sizes and without statistical treatments, and 2) more recent studies in which nestling diet is not examined in detail. For instance, all lepidopteran species are lumped into a single broad category (percentage of caterpillars; e.g., Blondel et al, 1991;Nour et al, 1998;Przybylo & Merilä, 2000;Tremblay et al, 2005;Massa et al, 2004). In the context of climate change, more detailed studies are necessary that address the effects of birds' preferences for some prey types (i.e., prey choice decisions) on the ability of different but similar species to cope with phenological changes in the underlying tropic levels (by, e.g., switching to alternative prey; see, e.g., Veen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(92.000: 43% P. halepensis, 39% P. pinea, 17% P. nigra). From an environmental point of view, af forestations did not increase biodiversity for two reasons: 1) effects of afforestation techniques re duced pre-existing biodiversity (Pasta & La Mantia 2001a, La Mantia & Pasta 2001; 2) current wooded areas consist of many exotic species, as Eucalyptus, or conifers (Pinus, Cedrus, Cupressus), often subjected to fires, almost completely lacking of naturalistic in terest in particular for flora biod iversity (Pasta & La Mantia 2001a, La Mantia & Pasta 2001 and fauna (Massa et al 2004).…”
Section: Changes In the Forestrymentioning
confidence: 99%
“…Other two passerines species were in creasing colonizing the same wood habitat, that is Regulus ignicapilla and Phylloscopus collybita. Other species (Cyanistes caeruleus and Parus major) in creased their population in function of silvicoltural treatment (Massa et al 2004). …”
Section: Increasing and Declining Selected Species Of Woodlandsmentioning
confidence: 99%